THE INFLUENCE OF LIQUIDITY, SOLVENCY AND PROFITABILITY ON COMPANY VALUE IN TELECOMMUNICATION COMPANIES THAT GO PUBLIC ON THE IDX FOR THE 2017-2021 PERIOD - Aca Aca; Amrizal Salida; Jumriah Basri (Universitas Ichsan Sidenreng Rappang, 2025)
This research aimed to determine the influence of liquidity, leverage and profitability on company value in telecommunications companies that go public on the Indonesia Stock Exchange in the 2017-2021 period. This research was a type of descriptive quantitative research. The population in this research was telecommunications companies that went public on the Indonesia Stock Exchange for the 2017-2021 period, totaling 19 companies. Based on the sampling technique using purposive sampling, a sample of 7 companies were obtained. Data collection techniques used documentation from financial reports published on the official website of the Indonesia Stock Exchange (www.idx.co.id). The analysis technique used multiple linear regression. The results of this research showed that: (1) Liquidity does not have a positive and significant effect on Company Value with a regression coefficient of 0.015 and a significance value of 0.977 > 0.05; (2) Solvency has a positive and significant effect on Company Value with a regression coefficient of 0.637 and a significance value of 0.001 < 0.05; (3) Profitability does not have a positive and significant effect on Company Value with a regression coefficient of 1.361 > 0.05 and a significant value of 0.227 > 0.05; (4) Liquidity, Solvency and profitability have a positive and significant effect on Company Value with a significance of 0.000 with an R2 value of 43.1%. Kata kunci: Likuiditas, Nilai Perusahaan, Profitabilitas dan Solvabilitas